Somatosensory evoked potentials after multisegmental upper limb stimulation in diagnosis of cervical spondylotic myelopathy. Issue 3 (March 1994) - Restuccia, D; Valeriani, M; Di Lazzaro, V; Tonali, P; Mauguière, F
Abstract : Radial, median, and ulnar nerve somatosensory evoked potentials (SEPs) were recorded, with non-cephalic reference montage, in 38 patients with clinical signs of cervical myelopathy and MRI evidence of spondylotic compression of the cervical cord. Upper limb SEPs are useful in spondylotic myelopathy because SEPs were abnormal in all patients for at least one of the stimulated nerves and SEP abnormalities were bilateral in all patients but one. Reduction of the amplitude of the N13 potential indicating a segmental dysfunction of the cervical cord was the most frequent abnormality; it occurred in 93.4%, 84.2%, and 64.5% of radial, median, and ulnar nerve SEPs respectively. A second finding was that the P14 far-field potential was more sensitive than the cortical N20 potential to slowing of conduction in the dorsal column fibres. The high percentage of N13 abnormalities in the radial and median rather than in the ulnar nerve SEPs correlated well with the radiological compression level, mainly involving the C5-C6 vertebral segments. Therefore the recording of the N13 response is a reliable diagnostic tool in patients with cervical spondylotic myelopathy and P14 abnormalities, though less frequent, can be useful in assessing subclinical dorsal column dysfunction.